2020
DOI: 10.1007/s10554-020-02100-3
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular strain values using 3D speckle-tracking echocardiography in healthy adults aged 20 to 72 years

Abstract: Three dimensional speckle tracking echocardiography (3D-STE) is a novel modality for the assessment of left ventricular strain (LVS). The aim of our study is to provide single vendor normative strain values measured with 3D-STE in healthy adult caucasians. One hundred fifty-five healthy subjects aged 20 to 72 years (≥ 28 subjects per decile) were prospectively included and examined with 2D and 3D transthoracic echocardiography. In 105 both 3D and 2D-STE were feasible (71%, mean age 44 ± 14 years, 51% female). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Measurements and normative values are vendor specific, and often only established in adult age ranges. Normative LV strain values are reported via 2-D TomTec CPA in healthy young adults in Mutluer et al, though normative pediatric strain values using TomTec CPA are only reported in smaller cohorts [ 31 33 ]. The lack of large pediatric datasets for strain using TomTec CPA specifically prompted our use of an age and gender matched control group to allow for the most accurate comparison, avoiding inter-vendor and inter-reader variability.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements and normative values are vendor specific, and often only established in adult age ranges. Normative LV strain values are reported via 2-D TomTec CPA in healthy young adults in Mutluer et al, though normative pediatric strain values using TomTec CPA are only reported in smaller cohorts [ 31 33 ]. The lack of large pediatric datasets for strain using TomTec CPA specifically prompted our use of an age and gender matched control group to allow for the most accurate comparison, avoiding inter-vendor and inter-reader variability.…”
Section: Discussionmentioning
confidence: 99%
“…To be able to compare the LAS and LASR data, we used a control group consisting of self-declared healthy volunteers, described previously. 11 …”
Section: Methodsmentioning
confidence: 99%
“…[13] The de nitions of LA strain, strain rate and volume are summarized in Supplementary table 1. Normative ranges for LA-S [13], LV-GLS [14], LV-SRe [15], and RV-FWLS [16] were extracted from the studies conducted in the same hospital.…”
Section: Speckle Tracking Analysismentioning
confidence: 99%